Impact of gender differences in salary / Jemaline Asan Gabra and Nazhatul Qamaria Ashiran - Gabra, Jemaline Asan; Ashiran, Nazhatul Qamaria (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2013)
This study will examine the impacts of gender differences in salary towards male and female worker in organization. We have developed a questionnaire consisting of three parts includes worker's demographic background, gender differences in salary system and the impacts of gender differences in salary. We choose male and female workers in Kota Kinabalu Industrial Park sdn.bhd. The research design is cross-sectional because we are using questionnaire to directly collecting data from them. We use the non-parametric test in order to see the significant correlation between gender differences in salary and the impacts towards job satisfaction, job performance and self-motivation of the workers.